Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1007/bf02983818
|View full text |Cite
|
Sign up to set email alerts
|

The Bisphosphonate Zoledronic Acid Induces Cytotoxicity in Human Myeloma Cell Lines with Enhancing Effects of Dexamethasone and Thalidomide

Abstract: Bisphosphonates have recently been introduced in the therapeutic armamentarium for long-term treatment of patients with multiple myeloma. These pyrophosphate analogs not only reduce the occurrence of skeletal events but also provide clinical benefit to patients and improve the survival of some of them. The existence of these capabilities raises the possibility that these compounds may have a direct antiproliferative effect on tumor cells. To investigate whether these drugs exert a direct antitumor effect, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 39 publications
4
41
1
Order By: Relevance
“…However, there was no mention of novel chemosensitizing effects of bisphosphonates (BPs) or possible mechanisms of action. This study supports the findings of other studies which showed that BPs act synergistically with other chemotherapeutic agents [2,3], a notion that further supports the combined use of BPs as chemosensitizing agents.…”
Section: To the Editorsupporting
confidence: 91%
See 1 more Smart Citation
“…However, there was no mention of novel chemosensitizing effects of bisphosphonates (BPs) or possible mechanisms of action. This study supports the findings of other studies which showed that BPs act synergistically with other chemotherapeutic agents [2,3], a notion that further supports the combined use of BPs as chemosensitizing agents.…”
Section: To the Editorsupporting
confidence: 91%
“…Although ZOL clearly has cytotoxic effects on prostate cancer cells in vitro, these may be mediated by the compound's ability to chelate calcium. Our previous study with EGTA, which also chelates calcium, demonstrated only a small effect on the reduction on cell number which remained significantly different from the greater effect observed following ZOL treatment [3]. Addition of EGTA to ZOL-containing cultures showed a significant decrease in cytotoxicity rather than an enhanced cytotoxic effect, which one would have expected if the mechanism was via calcium chelation.…”
Section: To the Editorcontrasting
confidence: 55%
“…Zoledronic acid has been shown to synergistically increase cancer cell death when combined with doxorubicin, paclitaxel, or cyclophosphamide in breast cancer cells (24)(25)(26); paclitaxel, etoposide, cisplatinum, and irinotecan in lung cancer cells (27); and dexamethasone in myeloma cells (28) in vitro. Combining zoledronic acid (250 μg/kg) with the oral fluoropyrimidine UFT (20 mg) daily decreased the number of bone metastases compared with single agents in the 4T1 mouse mammary tumor model (29).…”
Section: Introductionmentioning
confidence: 99%
“…The synergistic mechanism of zoledronic acid and radiation, however, is currently unknown. We recently showed an increase in the proportion of the cells in the S-phase by flow cytometric analysis of zoledronic acidtreated multiple myeloma cells, possibly due to a slower progression through the S-phase or a block between the S-phase and G 2 M-phase in the cell cycle [29]. This ability of the BPs to arrest the cells in the G 2 M-phase or prolong cell cycle progression raises the possibility of BPs as potential cell cycle radiosensitizers since G 2 and M cells are more sensitive than cells within other cell cycle phases [41].…”
Section: Bp and Radiotherapy Combination In Breast Cancermentioning
confidence: 99%
“…We have recently demonstrated that zoledronic acid induces antiproliferative and apoptotic effects on multiple myeloma cell lines in vitro, by activating protein kinase C, and increases the extracellular calcium concentrations, these effects being augmented with dexamethasone and thalidomide [29]. In addition, objective remission or inhibition of disease progression has been reported in patients with multiple myeloma who underwent pamidronate treatment alone [30].…”
Section: Antitumor Effects Of Bpsmentioning
confidence: 99%